(untitled) (Research, Society and Development, 2022)
E-cigarette use can weaken the respiratory system and compromise the immune response, thus, there is greater susceptibility to respiratory infections, such as that caused by COVID-19. In this sense, the objective of this study is to analyze the impact on the infection caused by COVID-19 in young people who use electronic cigarettes. As for the methodology, it is a systematic review of the literature that searched for articles in the Virtual Health Library (BVS), U.S. National Library of Medicine (PubMed) and Google Scholar with the following descriptors: “Vaping” AND “COVID-19”. Of the 321 articles found, 285 were excluded due to escape from the topic, duplicity and unavailability of the full text, and the final corpus consisted of 27 articles, which were categorized into two axes: (I) Effects of electronic cigarettes in increasing the risk of transmission, infection and complications by COVID-19 and (II) Pathophysiology of the consequences of electronic cigarettes in the body. Vaporization is related to the occurrence of serious lung injuries that can cause decreased airway resistance to pathogens, increasing susceptibility to infections and complications from COVID-19. Therefore, it is extremely important to understand the relationship between vaping use and COVID-19 to understand its impact.